The influence of preageing temperatures on the mechanical properties A1-5Zn-2Mg alloy - Avramović-Cingara, Gordana; Mihajlović, Aleksandar (Journal of Production Engineering, 1984)
The investigation was carried out on Al-4.52wt%Zn-2.03wt%Mg. Continuous heating from the first to the second precipitation step was applied. In order to determine the influence of the pre-ageing temperatures on the mechanical properties, the different temperature levels (60, 80, 100) were investigated. It was found that the optimum temperature is C. The electrical resistance measurements during isochronous ageing show that this temperature is associated with strong nucleation and growth of GP zones.